2021
DOI: 10.1111/1750-3841.15963
|View full text |Cite
|
Sign up to set email alerts
|

Auricularia auricula‐judae (Bull.) polysaccharides improve type 2 diabetes in HFD/STZ‐induced mice by regulating the AKT/AMPK signaling pathways and the gut microbiota

Abstract: Auricularia auricula‐judae is an edible fungus with high nutritional value due to abundant polysaccharides, and is acknowledged as traditional food and medicine in Asia. Polysaccharides from A. auricula (AAPs) are typically fungal polysaccharides and have a wide range of biological activities. It has been shown the potential of AAPs to improve diabetes as an effective adjuvant, but the underlying mechanism remains unclear. In this study, we explored the effects and potential mechanism of AAPs on type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
(53 reference statements)
1
14
1
Order By: Relevance
“…76 FNJ supplementation decreased the F/B ratio, which was consistent with other dietary modifiers. 2,24 Moreover, FNJ administration significantly raised certain beneficial bacteria genera in db/db mice such as Odoribacter, Rikenella, Muribaculum, and Anaerostipes, and mitigated pernicious bacteria Enterorhabdus. 2,23 Meanwhile, FNJ also increased the relative abundance of Alistipes, Colidextribacter, Mucispirillum, and Butyricicoccus and alleviated Limosilactobacillus, Ligilactobacillus, Candidatus-Arthromitus, [Eubacterium]-ventriosum-group, and Staphylococcus at the genus level.…”
Section: Papermentioning
confidence: 99%
See 3 more Smart Citations
“…76 FNJ supplementation decreased the F/B ratio, which was consistent with other dietary modifiers. 2,24 Moreover, FNJ administration significantly raised certain beneficial bacteria genera in db/db mice such as Odoribacter, Rikenella, Muribaculum, and Anaerostipes, and mitigated pernicious bacteria Enterorhabdus. 2,23 Meanwhile, FNJ also increased the relative abundance of Alistipes, Colidextribacter, Mucispirillum, and Butyricicoccus and alleviated Limosilactobacillus, Ligilactobacillus, Candidatus-Arthromitus, [Eubacterium]-ventriosum-group, and Staphylococcus at the genus level.…”
Section: Papermentioning
confidence: 99%
“…2,24 Moreover, FNJ administration significantly raised certain beneficial bacteria genera in db/db mice such as Odoribacter, Rikenella, Muribaculum, and Anaerostipes, and mitigated pernicious bacteria Enterorhabdus. 2,23 Meanwhile, FNJ also increased the relative abundance of Alistipes, Colidextribacter, Mucispirillum, and Butyricicoccus and alleviated Limosilactobacillus, Ligilactobacillus, Candidatus-Arthromitus, [Eubacterium]-ventriosum-group, and Staphylococcus at the genus level. LDA analysis proved that T2DM mice enriched in harmful bacteria Enterobacteriaceae, Klebsiella, and Klebsiella-pneumonia, while FNJ significantly upregulated Rikenellaceae.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that dietary polysaccharides with different structures could regulate the composition of intestinal flora precisely [ 13 , 14 ]. Xu et al found that Auricularia auricula polysaccharides (AAP) elevated intestinal flora diversity and optimized microbial composition and function in T2D mice, characterized by increased Lactobacillus and Bacteroides and decreased Clostridium and Allobaculum [ 15 ]; however, there are few studies on the regulatory effects of AAP on gut microbiota in normal mice, especially concerning AAP from the Qinba Mountains.…”
Section: Introductionmentioning
confidence: 99%